2007
DOI: 10.1007/s10974-007-9122-9
|View full text |Cite
|
Sign up to set email alerts
|

Activation of caspase 3, 9, 12, and Bax in masseter muscle of mdx mice during necrosis

Abstract: The mdx mouse, a model of muscular dystrophy, lacks dystrophin, a cell membrane protein. It is known that the lack of dystrophin causes muscle fiber necrosis from 2 weeks after birth, and the majority of necrotic muscle fibers are replaced by regenerated muscle fibers by 4 weeks after birth. A recent study indicated the possibility that mitochondria-mediated intracellular stress, a phenomenon similar to apoptosis, may be produced during muscle fiber necrosis, but did not analyze endoplasmic reticulum-mediated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 19 publications
3
16
0
Order By: Relevance
“…Importantly, BiP and cleaved caspase-4 were also elevated in muscle samples from DMD patients. The increase in caspase-12 is consistent with a previous study that found increased caspase-12 expression in the masseter of young mdx mice (38). Increased P-JNK, which is not specific to ER stress, has also been previously observed in 8-week-old mdx TA muscles (39) and 5-month-old mdx hearts (40).…”
Section: Discussionsupporting
confidence: 92%
“…Importantly, BiP and cleaved caspase-4 were also elevated in muscle samples from DMD patients. The increase in caspase-12 is consistent with a previous study that found increased caspase-12 expression in the masseter of young mdx mice (38). Increased P-JNK, which is not specific to ER stress, has also been previously observed in 8-week-old mdx TA muscles (39) and 5-month-old mdx hearts (40).…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, B10 mice showed normal skeletal muscle and immunolocalization of dystrophin. It has been reported that in somite-derived muscles of the extremities, muscle necrosis begins 2 weeks after birth, immediately followed by regeneration, and the majority of necrotic muscles are regenerated by 4 weeks after birth (Dangain and Vrbova, 1984;DiMario et al, 1991;Attal et al, 2000;Honda et al, 2007;Abe et al, 2007). We observed a similar pattern in Mdx mice, though over a different period of time, with complete muscle regeneration at 9 weeks.…”
Section: Discussionsupporting
confidence: 78%
“…Expression levels of caspase-3, caspase-9, and Bax expression levels have been shown to be significantly upregulated in the muscle of mdx mice [58]. An imbalance between the production and degeneration of myocytes, exacerbated by increased apoptosis and decreased regenerative capacity leads to atrophy in the skeletal muscle of mdx mice [59].…”
Section: Discussionmentioning
confidence: 99%